Embodied Action, Projection, and Institutional Action: The Exchange of Tools and Implements During Surgical Procedures. Issue 3 (16th March 2021) - Heath, Christian; Luff, Paul
ABSTRACT: There has been a long-standing interest in projection and the resources on which participants rely to produce and recognize the import and organization of turns at talk. Less attention has been paid to the character of the activity in which utterances form part and the ways in which embodied action enables the intelligibility, coordination, and in some cases, coproduction, of particular actions. In this article, we focus on specialized forms of embodied, institutional activity and focus in particular on simultaneity and the ways in which bodily action enables the progressive formation and reformation of an activity in the light of the (co)participants' emerging contributions. We address how the routine structure of particular tasks enables participants to anticipate, prepare for, and even initiate actions in advance of the relevant activity and in turn, how participants may seek to ameliorate the interactional import of potentially premature action. The articles explores the interplay of technical practice and interactional organization and points to the distinctive character of embodied action in understanding anticipation and coordination in complex forms of institutional interaction.